Nuclear orientation of152,154Tb in gadolinium - Ferencei, J; Finger, M; Dupák, J; Jankech, A; Koníček, J; Schus, F; Říkovská, J; Machová, A; Hamilton, D (Kluwer Academic Publishers-Plenum Publishers, 1981)
The anisotropy in the directional distribution of gamma-rays from the decay of152,154Tb oriented in a gadolinium matrix at low temperatures, has been measured at the angles of 0 and π/2 with respect to the applied magnetic field direction at temperature of (15±1) mK. Unambiguous values of spin have been deduced for several levels in152Gd. Multipole mixing ratios of many gamma-ray transitions occurring in152Gd have been found and results are compared with the similar transitions in150,154,156Gd and they are discussed in terms of the rotational-vibrational model and dynamic deformation theory based on the Strutinsky method. Our results confirm the spin value of 0 for 21·4 h isomer in154Tb and they establish the spin value of 3 for the 2277·0 and 2336·1 keV levels and the spin value of 4 for the 2416·3 keV level in154Gd. © 1981 Academia, Publishing House of the Czechoslovak Academy of Sciences.